Multiplicando esfuerzos para fortalecer la familia desde la orientación - Calderón Monge, Eliud (2009)
The proposal includes the systematization of a training experience where 35 teaching and administrative officials participated. They came from 9 elementary schools located in marginal communities, developed by a team of two school counselors whose main purpose was to encourage among the participants the development of skills that will let them design and apply activities in the field of “parents’ school”. Thus, an educational counseling proposal has been modeled in order to reach greater coverage and efficiency of the counseling work with families being done from within the school. Moreover, what’s being sought is the promotion of healthy family relationships that contribute to the family’s wholeness and well being and therefore to the appropriate academic and social development of their children.